Protein and Iron Intake Among Female Adolescents in SMP Negeri 10 in Gorontalo City - Indra Domili; Firka Kartasasmita Djafar; Fitri Yani Arbie; Misnati Misnati (Poltekkes Kemenkes Gorontalo, 2021)
Female adolescents are prone to anaemia. This situation can be caused most of them consume more vegetables than meat. The consideration behind such a diet is the desire to be slim. However, a diet like this will put the menstrual cycle at risk, and the excretion of iron through faeces. This study aims to determine the intake of protein and iron in adolescent girls at SMP Negeri 10 Kota Gorontalo. This survey research used a descriptive method. All data were collected using a 24-hour recall form which was distributed to all young women at the study location. This research was conducted in October 2019. A total of 60 students were selected as samples. The results showed that protein intake in young women was in the very low category. Meanwhile, the iron intake in adolescent girls was in the low category. Overall, the study participants' protein and iron intake were low.